A Cross-Sectional Survey of Biosafety Professionals Regarding Genetically Modified Insects. (March 2020) - O'Brochta, David A.; Tonui, Willy K.; Dass, Brinda; James, Stephanie
Background: Genetic technologies such as gene editing and gene drive create challenges for existing frameworks used to assess risk and make regulatory determinations by governments and institutions. Insect genetic technologies including transgenics, gene editing, and gene drive may be particularly challenging because of the large and increasing number of insect species being genetically modified and the degree of familiarity with these organisms and technologies by biosafety officials charged with making containment decisions. Methods: An anonymous online survey of biosafety professionals was distributed to the membership of ABSA International, a global society of biosafety professionals, to investigate their perspectives on their preparedness to meet these new challenges. Results: Existing guidance used to make containment decisions for nongenetically modified insects was widely seen as adequate, and most respondents thought the available guidance for making containment decisions for genetically modified insects with and without gene drives was inadequate. Most respondents reported having less confidence in their decisions concerning containment of genetically modified insects compared to decisions involving genetically modified microbes, (noninsect) animals, and plants. Conclusions: These results reveal a need for additional support for biosafety professionals to improve the quality of and confidence in containment decisions regarding genetically modified insects with and without gene drive. These needs might be addressed by increasing training, updating existing guidance, creating new guidance, and creating a third-party accreditation entity to support institutions. Sixty percent of the respondents said they either would or might use a voluntary third-party accreditation service to support insect containment decisions.